Seismic Performance Analysis of Steel Truss Coal Conveying Trestle Based on Multisensor Data Fusion - Bo-yu Yao (Discrete Dynamics in Nature and Society)
Coal ranks first in the energy demand of our country, and it also plays an unshakable role in promoting national defense and economic development. Coal conveying trestle is the link and lifeline in the process of coal production. Once it is damaged by an earthquake, it will cause great losses in the production of coal enterprises. Therefore, it is of great significance to analyze the seismic performance of long-span coal conveying trestle and apply it to engineering design. To solve this problem, an analysis method based on the combination of field measurement and finite element simulation is proposed. Firstly, multisensor data fusion is introduced, and the finite element model for the dynamic characteristic analysis of long-span coal conveying trestle is constructed. Then, based on multisensor data fusion, the dynamic characteristics of long-span coal conveying trestle are measured. Finally, the model is modified based on the measured results, and the seismic performance of long-span coal conveying trestle under strong earthquake is analyzed. The results show that the model can accurately characterize the seismic performance of long-span coal handling trestle, which provides an effective numerical simulation method for the engineering design of coal handling trestle.